Teaching Reading Comprehension by Using Some Methods in Senior High Schools - Saori, Sopian (Journal of Languages and Language Teaching, 2022)
The study aimed to figure out the methods used by English teachers in teaching reading comprehension and how they applied them. The main purpose of the study was to describe the methods used by english teachers and reveal the strength and weakness of the methods. This research was a descriptive qualitative research. The design of the study was a case study. The participants of the research were two English teachers who teach in the second grade of senior high schools. Each English teacher had eight meetings that observed by the researcher. To collect the data, there were research instruments: observation, document analysys checklist and interview. They were used to find out the method used and how the English teachers applied them in teaching reading comprehension. The result of the study showed that both teachers used almost the same methods such as, grammar-translation method, scaffolding, and mind mapping. The difference was in the step of the implementation. In addition, the findings showed that the most appropriate method in teaching reading comprehension was the grammar-translation method since it helped students comprehend the text. There were several students who still found it hard to understand the materials of the lessons. Teachers were supposed to make sure that all students have understood the whole text or not and they should observe the students’ situation and needs so that the teaching and learning process can run well and use better methods of teaching.